The Role of Non-Governmental Organisations in the Development of Rural Tourism in Vojvodina (Serbia) - Jegdić, Vaso; Škrbić, Iva; Milošević, Srdjan (Eastern European Countryside, 2024)
Sustainable rural tourism requires a high rate of local participation to achieve planning and development objectives. Particularly significant is the role of local non-governmental organisations (NGOs) to facilitate and plan useful projects pertinent to rural development and tourism that aim to include the local population in such activities. During the last two decades, the increasing number of NGOs in developing countries has led to them becoming influential actors in sustainable development in many fields and bearers of various ideas, projects and other activities. This is particularly evident in rural tourism, where NGOs have become prominent in the field of rural attractions as well as in the training and capacity building of local communities. Tens of NGOs whose activities are essentially directed towards rural development are active in Vojvodina, however, their actual role in sustainable tourism is not completely understood. This study regarding the NGOs concerned with rural development aimed to identify, analyse and evaluate the role of non-governmental organisations in sustainable rural tourism in Vojvodina. The starting presumption was that NGOs have a clear and significant role in the sustainable development of rural tourism in Vojvodina. The basic methods and techniques of data collecting were observation and analysis of documents and the techniques of standardised interviews, with elements of in- depth interviews. This research has shown that the role of the non-governmental sector in the development of tourism in Vojvodina is not visible and well defined, but also that some NGOs achieve high-quality results.